Commercialization‐Driven Electrodes Design for Lithium Batteries: Basic Guidance, Opportunities, and Perspectives. Issue 43 (5th August 2021) - Cao, Chunyan; Liang, Fanghua; Zhang, Wei; Liu, Hongchao; Liu, Hui; Zhang, Haifeng; Mao, Jiajun; Zhang, Yanyan; Feng, Yu; Yao, Xi; Ge, Mingzheng; Tang, Yuxin
Abstract: Current lithium‐ion battery technology is approaching the theoretical energy density limitation, which is challenged by the increasing requirements of ever‐growing energy storage market of electric vehicles, hybrid electric vehicles, and portable electronic devices. Although great progresses are made on tailoring the electrode materials from methodology to mechanism to meet the practical demands, sluggish mass transport, and charge transfer dynamics are the main bottlenecks when increasing the areal/volumetric loading multiple times to commercial level. Thus, this review presents the state‐of‐the‐art developments on rational design of the commercialization‐driven electrodes for lithium batteries. First, the basic guidance and challenges (such as electrode mechanical instability, sluggish charge diffusion, deteriorated performance, and safety concerns) on constructing the industry‐required high mass loading electrodes toward commercialization are discussed. Second, the corresponding design strategies on cathode/anode electrode materials with high mass loading are proposed to overcome these challenges without compromising energy density and cycling durability, including electrode architecture, integrated configuration, interface engineering, mechanical compression, and Li metal protection. Finally, the future trends and perspectives on commercialization‐driven electrodes are offered. These design principles and potential strategies are also promising to be applied in other energy storage and conversion systems, such as supercapacitors, and other metal‐ion batteries. Abstract : This review presents the state‐of‐the‐art developments on constructing commercialization‐driven electrodes for high energy density lithium batteries. The basic guidance and critical challenges on constructing high mass loading electrodes are discussed. Accordingly, the corresponding strategies are proposed to overcome these challenges.